Towards a green world: how new urbanization affects green total factor carbon productivity - Wang, Xiaohong; Li, Xuanting (Frontiers in Environmental Science, 2025)
IntroductionNew urbanization is a powerful support for regional economic growth and green transformation.MethodsIn this paper, we select data from 237 cities at prefecture level and above in China from 2010 to 2021 for quasi-experimental design, and investigate the effects of new urbanization policy pilots on urban green total factor productivity (GTFP) and its mechanism by constructing a multi-period difference-in-differences model.ResultsThe study finds that: a) the construction of new urbanization has a positive impact on promoting urban GTFP, and this result is verified by a series of robustness tests; b) the promotion of industrial structure upgrading, the facilitation of green technological innovation, and the reduction of the degree of resource mismatch all partially mediate the relationship between new urbanization and urban GTFP; c) environmental regulation and market integration both modulate the relationship between the construction of new urbanization and urban GTFP in positive directions; d) heterogeneity analysis shows that, in terms of the two-dimensional city attributes of ‘location-characteristics’, the increase in GTFP is more significant in eastern and central cities, and in non-resource cities; e) further analysis shows that the pilot policies of new urbanization have a spatial spillover effect on GTFP, and the policy spillover effects are mainly affected through mechanisms such as industrial structure upgrading in neighboring municipalities.DiscussionThis study provides new ideas for the next stage of sustainable regional green development in China, thus promoting China's high-quality development with theoretical and practical significance.